Religious conflict in Brazil : Protestants, Catholics, and the rise of religious pluralism in the early twentieth century - Helgen, Erika (Yale scholarship online., 2020)
The story of how Brazilian Catholics and Protestants confronted one of the greatest shocks to the Latin American religious system in its 500-year history. This innovative study explores the transition in Brazil from a hegemonically Catholic society to a religiously pluralistic society. With sensitivity and nuance, Erika Helgen shows that the rise of religious pluralism was fraught with conflict and violence, as Catholic bishops, priests, and friars organized intense campaigns against Protestantism. These episodes of religious violence were not isolated outbursts of reactionary rage, but rather formed part of a longer process through which religious groups articulated their vision for Brazil's national future.